THE EFFECTIVENESS AND CORRESPONDING ENERGY PARAMETERS OF HIGH-INTENSITY FOCUSED ULTRASOUND IN THE TREATMENT OF HEMANGIOMAS IN INFANTS (World Bulletin of Public Health, 2024)
Hemangioma in children is a benign neoplasm that manifests itself in the first few weeks after birth. According to a study by the Medical College of Wisconsin, boys suffer from the disease 3 times less often than girls. The tumor is localized on the neck, head, face, arms and legs, in rare cases it develops on the larynx or liver. Often, the hemangioma goes away on its own. But sometimes it causes bleeding and complications, such as destruction of cartilage of the lips, nose, ears and strabismus. Often, a hemangioma is a sign of a disease, for example, Castroviejo syndrome. Therefore, when the first symptoms appear, an examination is recommended. Treatment of hemangiomas in children is different: if necessary, the doctor will individually select the procedures and timing
Keywords: children; hemangioma; ultrasound treatment.